COMPUTERIZED LENDING SYSTEM ON COOPERATIVE EMPLOYEES PT TALAYA - Marjuki Marjuki; Sahni Damerianta Purba (Jurnal Sistem Informasi, 2000)
Cooperatives have been using a computerized system in carrying out various activities, but its utilization is not optimal. as in the loan service activities is still done manually, so that in making the report takes a long time. to take advantage of the speed accuracy in loan service